2014
DOI: 10.1111/ajt.12662
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequences Incurred by Living Kidney Donors: A Canadian Multi-Center Prospective Study

Abstract: Some living kidney donors incur economic consequences as a result of donation; however, these costs are poorly quantified. We developed a framework to comprehensively assess economic consequences from the donor perspective including out-of-pocket cost, lost wages and home productivity loss. We prospectively enrolled 100 living kidney donors from seven Canadian centers between 2004 and 2008 and collected and valued economic consequences ($CAD 2008) at 3 months and 1 year after donation. Almost all (96%) donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 17 publications
6
94
0
1
Order By: Relevance
“…The disparities workgroup supports the recommendations of Tushla et al (44) from the Consensus Conference to achieve financial neutrality for living donors. These recommendations include legislative protection from job loss and insurance discrimination as a result of living donation as well as the creation of a toolkit to better educate transplant centers and potential living donors about the financial effect of donation and potential resources to mitigate cost.…”
Section: Recommendation 1: Remove Financial Disincentives To Lkdmentioning
confidence: 67%
See 3 more Smart Citations
“…The disparities workgroup supports the recommendations of Tushla et al (44) from the Consensus Conference to achieve financial neutrality for living donors. These recommendations include legislative protection from job loss and insurance discrimination as a result of living donation as well as the creation of a toolkit to better educate transplant centers and potential living donors about the financial effect of donation and potential resources to mitigate cost.…”
Section: Recommendation 1: Remove Financial Disincentives To Lkdmentioning
confidence: 67%
“…The LDKT and LKD financial concerns of patients and potential donors are not unfounded (41)(42)(43). The workgroup noted the likelihood that the financial effect of LKD is a significant driver of disparities in LDKT, both for those in lower socioeconomic classes and for many members of minority groups.…”
Section: Incomementioning
confidence: 99%
See 2 more Smart Citations
“…These may include direct out-of-pocket expenses (i.e., travel, lodging, meals, parking, dependent care, and some uncovered medical expenses) and indirect costs (i.e., lost wages, use of employer-sponsored paid time off, and effect of insurability or premium rates) (Table 1) (4). Total estimated costs for LKDs range from $0-$20,000, with an average of approximately $5000 (4,16,17). In a 2014 Canadian study, Klarenbach et al reported that 96% of LKDs had experienced negative financial consequences from donation, with 47% reporting lost wages (16).…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%